Tinjauan Information Common pada Desain dan Fasilitas di Library and Knowledge Center, Binus University - Erika, Erika; Utami, Vilianty Rizki (Jurnal Ilmu Informasi, Perpustakaan, dan Kearsipan, 2020)
This research aims to examine the design and facilities of the Library and Knowledge Center (LKC) BINUS University Library using information common concept. The method of this research is quantitative by spread the questionnaire to library users at BINUS University. The respondent consists of students, lecturers, and employees at BINUS University. There are 122 valid questionnaires that have been processed. The result that has been obtained is about the design and facilities based on the trend of LKC BINUS University users. The result shows that not all LKC in BINUS University has implemented information common criteria in their design and facilities. The survey data shows most of the respondents argue that study area needs to be increased to support the need for study and research.